Enhancement of electrochemical performance of nickel cobalt layered double hydroxide@nickel foam with potassium ferricyanide auxiliary electrolyte. (1st December 2017) - Lamiel, Charmaine; Nguyen, Van Hoa; Hussain, Iftikhar; Shim, Jae-Jin
Abstract: Metal oxide nanostructures have been studied widely to overcome the limitations in the capacitance of the carbon-based supercapacitor electrode materials. An electrode with a very porous 3D structure is preferred to facilitate the mass transfer of large electrolyte ions. In this study, highly nanostructured, binder-free Ni-Co-based pseudocapacitive electrodes were synthesized directly on porous 3D structured nickel foam (NF) current collectors using low-power microwave irradiation. The electrochemical performance of the Ni-Co layered double hydroxide (Ni-Co-LDH) showed better performance than Ni-Co oxide (Ni-Co-O) with the further addition of redox additive/active electrolytes, such as K3 Fe(CN)6 . The specific capacitances of 4664 F g −1 for Ni-Co-LDH and 1758 F g −1 for Ni-Co-O at 5 mA cm −2 in the KOH/K3 Fe(CN)6 electrolyte were improved greatly compared to the values of their corresponding materials in the conventional KOH electrolyte (2875 and 250 F g −1, respectively). Interestingly, the Ni-Co-LDH//AC asymmetric device exhibited a specific capacitance of 108.9 F g −1 and an energy density of 38.7 Wh kg −1 with a stability of 61.9% after 5000 cycles. The facile yet cost-effective synthesis of nanostructured electrodes provides a versatile approach for the design of high-performance pseudocapacitive electrodes for future energy-storage systems. Highlights: Binder-free 3D Ni-Co LDH nanoflakes on Ni foam were synthesized under microwave. Ni-Co-LDH had a high specific capacitance 2875 F g −1, while Ni-Co-O had 250 F g −1 . The Specific capacitance increased from 2875 to 4664 F g −1 by adding K3 Fe(CN)6 . 91.1% of capacitance of Ni-Co-LDH was retained after 3000 cycles in KOH/K3 Fe(CN)6 . The Ni-Co-LDH//AC asymmetric device showed an energy density of 38.7 Wh kg −1 .